2017
DOI: 10.1371/journal.pone.0185130
|View full text |Cite
|
Sign up to set email alerts
|

Application of Raman spectroscopy in type 2 diabetes screening in blood using leucine and isoleucine amino-acids as biomarkers and in comparative anti-diabetic drugs efficacy studies

Abstract: Diabetes is an irreversible condition characterized by elevated blood glucose levels. Currently, there are no predictive biomarkers for this disease and the existing ones such as hemoglobin A1c and fasting blood glucose are used only when diabetes symptoms are noticed. The objective of this work was first to explore the potential of leucine and isoleucine amino acids as diabetes type 2 biomarkers using their Raman spectroscopic signatures. Secondly, we wanted to explore whether Raman spectroscopy can be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…The tentative assignments of the bands are displayed in Table . The PCA results indicated two things, first, that the antidiabetic effects of the herbal extract Rotheca myricoides Hochst were comparable with those of the commercially available drug pioglitazone, and second, it showed that Raman spectroscopy can be utilized in comparative efficacy studies between new antidiabetic drugs the commercially available conventional variants as was also shown in Birech et al…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The tentative assignments of the bands are displayed in Table . The PCA results indicated two things, first, that the antidiabetic effects of the herbal extract Rotheca myricoides Hochst were comparable with those of the commercially available drug pioglitazone, and second, it showed that Raman spectroscopy can be utilized in comparative efficacy studies between new antidiabetic drugs the commercially available conventional variants as was also shown in Birech et al…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we show that Raman spectroscopy can be an alternative technique for performing quick and label‐free detection of diabetes (or prediabetes) in blood with Raman spectral bands associated collectively with valine, leucine, isoleucine, creatine (creatine monohydrate), and sugar (glucose and fructose) as biomarkers. In Birech et al, it was shown that the intensity of Raman bands associated with isoleucine and leucine is different between blood from diabetic, treated, and nondiabetic rats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectra were measured using confocal Raman system (STR, Seki Technotron Corp) equipped with a 785‐nm laser and a spectrometer (Princeton Instruments). Before every experimental session, the Raman spectrometer was first calibrated using the 520 cm −1 band of a silicon . The experimental parameters for this study were as follows: grating, 600 groves/mm; centre wavelength, 850.97 nm (980 cm −1 ); excitation power at sample position, ~9 mW; spot size at sample position, ~65 μm; exposure time, 10 s; spectral accumulation, 5 s; and ×10 microscope objective (Olympus MPlanFN, 0.3NA).…”
Section: Methodsmentioning
confidence: 99%